Analisis Kebutuhan Materi Literasi Keuangan Dasar untuk Meningkatkan Kompetensi Keuangan Dasar pada Wirausahawan Muda - Sheila Febriani Putri; Mochammad Galih S Wicaksono; Nila Cahayati (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2021)
Improving human resources can never be separated from the process of educational activities. The role of education is expected to produce a generation that is superior, highly insightful, and has competitiveness to face the global era. Entrepreneurship is one of the subjects that must be taken by students. In practice, students are given the opportunity to go into the field to create a business according to their field or expertise. There is an assumption that business is only used as a sideline to meet the necessities of life or just to achieve personal pleasure to buy consumer goods. To overcome the problems faced by young entrepreneurs, especially students, a comprehensive material is needed to support knowledge and ability in entrepreneurship. The purpose of this study was to identify the financial literacy materials needed in entrepreneurship courses. The research data was obtained from the results of in-depth interviews with students who have taken entrepreneurship courses and have businesses and lecturers who are lecturers in entrepreneurship courses. The results of the study stated that there needs to be a balance between material on financial literacy and the depth of material related to financial management and business financing. In further development research, further developments related to planning, implementation and evaluation of financial literacy materials in entrepreneurship courses can be carried out as well as a more in-depth analysis of material development trial activities. The development of technology-based materials is expected to be the next alternative solution for the application of financial literacy materials in this course.